PW 1352 Self-harm behaviors and mental health among children and youth exposed to violence in early life. Findings from the violence against children surveys (VACS). (November 2018) - Villaveces, Andrés; Palomeque, Francisco; Espitia, Victoria Eugenia; Kress, Howard; Padilla, Mabel
Abstract : This study focuses on establishing the relationship between exposure to physical, sexual and emotional violence in childhood and mental health and suicidal outcomes in young adulthood. Using data from the Malawi and Nigeria Violence Against Children Surveys (VACS), which are nationally representative surveys of youth ages 13–24, we examine the association between exposure to physical, sexual, and emotional violence and witnessing violence before age 18, and self-harm, suicidal attempts, suicidal ideation and mental distress at ages 18–24. We hypothesize that individuals with exposure to childhood violence are more likely to experience all forms of suicidal and mental health outcomes. Analyses will further examine certain demographic characteristics influence the relationship between childhood violence exposure and suicide and mental health outcomes. For these analyses, multivariable regression methods will assess whether marital status and closeness with one or both parents modify the relationship between childhood violence exposure and mental health and suicide in young adulthood. These results have the potential to inform policy and programmatic strategies to promote health and well-being among children and youth.